Working with Allies and Partners A Cost-Based Analysis of U.S. Air Forces in Europe - Moroney, Jennifer D. P. (RAND Corporation, 2012)
U.S. Air Forces in Europe seeks to build partnerships and partner capacity in Europe. This report characterizes the current policy debate on security cooperation and force posture in Europe, develops a framework to describe the current approach and environment for the USAF in Europe, defines alternative postures for conducting activities, and recommends efficiencies to improve them.